THE CORRELATION BETWEEN READING ANXIETY AND READING COMPREHENSION ACHIEVEMENT EFL OF MAN 2 PALEMBANG - Annura, Tasya; Warna, Dewi; Sartika, Eka (Premise: Journal of English Education and Applied Linguistics, 2024)
Reading anxiety refers to the fear learners experience when reading a foreign language, impacting both the mind and body. This anxiety leads to cognitive, physical, and emotional problems, hindering students' ability to understand and extract information from texts, which significantly affects their reading achievement. This research examined the correlation and influence between students' reading anxiety and reading comprehension achievement among eleventh-grade students at MAN 2 Palembang. This study employed a quantitative, non-experimental research design utilizing a correlational approach. The study focused on eleventh-grade students from MAN 2 Palembang, with a sample of 102 students selected using convenience sampling. This study utilized the FLRAS Questionnaire, developed by Saito et al. (1999), and a reading test to gather data. The Pearson product-moment correlation was used with SPSS 26 to evaluate variable relationships. The findings indicated a moderate relationship between students' reading comprehension proficiency and reading anxiety level, with the correlation coefficient or R-value (0,522) higher than r-table (0,192). Furthermore, the findings suggested that students' reading anxiety substantially impacted their reading comprehension achievement, whose value (6,114) was higher than t-table(1,984)and sig. Value (0,000) was lower than probability (0,05). It could be proved that different levels of reading anxiety had a significant correlation to the student's reading comprehension achievement. The study revealed text features as the primary cause of students' foreign language reading anxiety, offering potential pedagogical benefits for future research and students.